Pengabdian Masyarakat: Membangun Desa melalui Inovasi Budidaya Magot Sebagai Upaya Pencegahan dan Penanganan Stunting untuk membentuk Lingkungan dan Masyarakat yang Lebih Sehat - Heny Supriana; Eri Fitriani; Mohammad Wildanul Khoufi; Muhammad Ridwan Abdullah; Suwahono (Pemberdayaan Masyarakat : Jurnal Aksi Sosial, 2024)
This research aims to see how the social conditions of the community in Darupono Village are the problems experienced by the village community and how the solutions are carried out by KKN MIT UIN Walisosongo Semarang students in their service in the community. The method used in community service is an extension method in the form of education and training by KKN students to the Darupono Village Community. The result of the service carried out is that there are still children who experience stunting in Darupono Village, so efforts are needed to prevent and handle stunting in Darupono Village